Early childhood infections and risk of schizophrenia - Liang, Wenbin; Chikritzhs, Tanya (Elsevier Ireland Ltd, 2012)
The association between early childhood infections and the risk of schizophrenia is not clear, and this study aimed to investigate the association between childhood infections and the risk of schizophrenia in a population-based Australia male cohort. A population-based cohort of males born between 1980 and 1984 in Western Australia was identified using birth registry records and followed-up until December 31st, 2009 or death using linked health data available through the Western Australian Data Linkage System. The associations between hospitalized infections occurring during 0–3 yr of age and risk of schizophrenia were assessed with stratified analysis and multivariate logistic regression models. Analysis was further repeated to assess the effect of hospitalized intestinal infections (gastroenteritis) and respiratory infections. It was observed that male participants with two or more hospitalizations for infections before the age of three had an 80% higher risk of schizophrenia, and these findings remained when the analysis was limited to intestinal infections and acute respiratory infections. These findings support the hypothesis that infections during early childhood may lead to the onset of schizophrenia in later life.